2020
DOI: 10.1097/bpb.0000000000000832
|View full text |Cite
|
Sign up to set email alerts
|

Predictive ability of scoring systems towards casting in treatment of idiopathic clubfoot by the Ponseti method in infants

Abstract: A prospective study to find a correlation between the severity of clubfoot and the number of casts required for the correction was conducted. The relationship of early relapse with the severity of the deformity was also studied. A total of 42 infants (61 feet) with primary and idiopathic clubfeet were included in the study. Previously treated and clubfeet due to secondary causes were excluded. All clubfeet were treated by the Ponseti method, and the Pirani score, Dimeglio score and Foot Bimalleolar (FBM) angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“… 25 , 26 However, assessing FAO compliance and initial severity scores is subjective. 8 Radiographs can be routinely used in clinical practice and represent an objective evaluation method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 25 , 26 However, assessing FAO compliance and initial severity scores is subjective. 8 Radiographs can be routinely used in clinical practice and represent an objective evaluation method.…”
Section: Discussionmentioning
confidence: 99%
“…Only children with a confirmed diagnosis of IC younger than 90 days at the time of first cast application and who had not received any previous orthopedic treatment were included in the study, as well as patients who (1) had to undergo AP and lateral foot radiographs less than 3 months after Achilles tendon lengthening, (2) had to wear the FAO up to 4 years of age, and (3) had to have at least 7 years of clinical follow-up. Additional information such as the severity of the deformity according to Dimeglio’s and Pirani’s classification systems, 7 , 8 number of casts, total time in cast, need for percutaneous Achilles tenotomy, adherence with post-correction brace, complications, relapses, and need for further surgical interventions was collected from the charts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not observe any wound or plaster-related complications in any of the feet. Studies have shown that the initial Pirani score correlates with radiological parameters but is not necessarily correlated to the final outcome in terms of the number of casts required for correction [28,29]. At the final follow-up, all the feet had become plantigrade with a Pirani score of zero, and there were no recurrences.…”
Section: Discussionmentioning
confidence: 99%